An Index for Transparency for Inflation-Targeting Central Banks : Application to the Czech National Bank - Al-Mashat, Rania; Bulir, Ales.; Dincer, N. Nergiz; Hledik, Tibor (Washington, D.C. : International Monetary Fund, 2018)
This paper develops a new central bank transparency index for inflation-targeting central banks (CBT-IT index). It applies the CBT-IT index to the Czech National Bank (CNB), one of the most transparent inflation-targeting central banks. The CNB has invested heavily in developing a Forecasting and Policy Analysis System (FPAS) to implement a full-fledged inflation-forecast-targeting (IFT) regime. The components of CBT-IT index include measures of transparency about monetary policy objectives, the FPAS designed to support IFT, and the monetary policymaking process. For the CNB, all three components have shown substantial improvements over time but a few gaps remain. The CNB is currently working on eliminating some of these gaps.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Deflation; Inflation; Price Level